Status Level of Total Mercury (T-Hg) in Barracuda (Sphyraena putnamae) from the Gulf of Thailand - Ritonga, Irwan Ramadhan; Bureekul, Sujaree; Luadnakrob, Pontipa; Sompongchaiyakul, Penjai (Trends in Sciences, 2023)
Mercury a major contributor to global environmental pollution and a source of human health issues and could have been transferred to the environment via bioaccumulation in food chain and trophic levels in aquatic environments. Barracuda (Sphyraena putnamiae) of different sizes were caught from various locations from the Gulf of Thailand (GoT) and determined for total mercury (T-Hg) using a direct thermal decomposition and gold amalgamation trapped mercury analyzer and evaluated for the accumulative human health risk for consumption. The range of T-Hg in edible muscle was from 9.58 to 314 µg/kg wet weight with an average of 59.1 ± 66.2 µg/kg wet weight, respectively. T-Hg in Barracuda caught from the middle and the lower GoT was found with a higher concentration than the upper GoT, which might be influenced by internal anthropogenic activities in the GoT and external sources from the land via river runoff. Fish length, weight, feeding habit and habitat were those influencing factors that significantly related to T-Hg accumulation in Barracuda. Risk assessment revealed that most of Barracuda had the estimated daily intake (EDI) values (0.03 µg/kg bodyweight per day) lower than provisional tolerable daily intake ((PTDI); 0.23 µg/kg bodyweight per day) and hazard quotient (HQ) was lower than 1, indicating no potential risk for adults associated with consumption the muscle of Barracuda muscle from the GoT. The maximum allowable daily consumption (MSDC) for Barracuda was 0.54 kg per day. HIGHLIGHTS Total mercury (T-Hg) in the muscle of Barracuda Sphyraena putnamae caught during a research survey in the Gulf of Thailand were analysed There was correlations between T-Hg accumulations in Barracuda; and fish size, feeding habits and habitat T-Hg content in fish varied by sampling sites, there it was influenced by T-Hg accumulation from anthropogenic activities No adult health risk via consumption of the T-Hg exposed Barracuda from the Gulf GRAPHICAL ABSTRACT